Identifikasi Bakteri pada Alat-Alat Medis Bedah Minor di Ruang UGD Puskesmas Pahandut Kota Palangka Raya: Identification of Bacteria on Minor Surgical Medical Devices in the er of Pahandut Public Helath Center Palangka Raya - Sherly Marselina; Natalia Sri Martani; Silvani Permatasari (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2023)
Background: HAIs are infections that are obtained from hospitals or other health care facilities, such as health centers. According to the Ministry of Health, in Indonesia it reaches 15.74%, much higher than in developed countries, which ranges from 4.8 to 15.5%. According to the Indonesian Ministry of Health, the average is 8.1%. At the Puskesmas, the Emergency Unit (ER) is the place most at risk for HAIs, for patients undergoing treatment using less sterile equipment, such as minor surgical equipment. Object: To determine the presence or absence of bacteria and to identify the types of bacteria in minor surgical medical devices in the ER Pahandut Public Health Center, Palangka Raya City. Methods: This study used a descriptive quantitative design method, to determine the presence or absence of bacteria in sterilized minor surgical medical devices. Results: The identification results found gram-positive bacteria in 3 samples of minor surgical instruments, namely 2 samples identified as Staphylococcus aureus and 1 sample identified as Streptococcus sp. Conclusion : There are bacterial contaminants in minor surgical medical devices used in the ER Pahandut Public Health Center, Palangka Raya City.